2021
DOI: 10.20882/adicciones.1583
|View full text |Cite
|
Sign up to set email alerts
|

Documento de consenso sobre asma y tabaquismo del Foro Autonómico de Asma de la SEPAR

Abstract: Documento de consenso sobre asma y tabaquismo del Foro Autonómico de Asma de la SEPAR

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 100 publications
0
1
0
3
Order By: Relevance
“…Fielding [ 18 ] et al found that a 10% reduction in%FEV1 between baseline and 3months was associated with 21% increased odds for having poor asthma control (95% CI 0-45) 6 months after baseline; even within the “normal range” (80-120%), FEV1%pred is still associated with increased risk of late asthma exacerbation and uncontrolled asthma. Smoking in asthmatic patients can exacerbate the decline of lung function indicators, including FEV1 % pred and FEV1, and this deterioration is correlated with the amount of smoking [ 6 , 19 , 20 ], whereas FEV1%perd can be improved with asthma control [ 21 ]. Therefore, dynamic detection of changes in FEV1%pred can effectively reflect the impairment of lung function and the level of asthma control in asthmatics who smoke.…”
Section: Discussionmentioning
confidence: 99%
“…Fielding [ 18 ] et al found that a 10% reduction in%FEV1 between baseline and 3months was associated with 21% increased odds for having poor asthma control (95% CI 0-45) 6 months after baseline; even within the “normal range” (80-120%), FEV1%pred is still associated with increased risk of late asthma exacerbation and uncontrolled asthma. Smoking in asthmatic patients can exacerbate the decline of lung function indicators, including FEV1 % pred and FEV1, and this deterioration is correlated with the amount of smoking [ 6 , 19 , 20 ], whereas FEV1%perd can be improved with asthma control [ 21 ]. Therefore, dynamic detection of changes in FEV1%pred can effectively reflect the impairment of lung function and the level of asthma control in asthmatics who smoke.…”
Section: Discussionmentioning
confidence: 99%
“…Las exposiciones al tabaco, a la marihuana o a los nuevos dispositivos de liberación de nicotina impactan negativamente en el control de la enfermedad, así como modifican o alteran la respuesta inmunitaria y los biomarcadores utilizados para su fenotipificación 17 , 18 , 20 , 21 . Por lo tanto, es necesario mejorar el abordaje del asma de los pacientes fumadores, así como el tratamiento del tabaquismo en dichos pacientes 22 .…”
Section: Highlights En El áRea De Asmaunclassified
“…Por todo ello, al cese del hábito tabáquico se le concede un alto nivel de prioridad en las guías de asma Global Initiative for Asthma (GINA) y Guía Española para el Manejo del Asma (GEMA) 4 , 5 , siendo uno de los indicadores de calidad asistencial en asma 7 . Además, se recomienda el cese de este hábito como parte esencial en el consenso de manejo de pacientes con asma y hábito tabáquico del 2020, promovidos por las Áreas de Asma y de Tabaquismo de la SEPAR 82 .…”
Section: Abordaje No Farmacológico Del Asma Desde Enfermeríaunclassified
“…Esta terapia debe constar de dos componentes fundamentales: estrategia conductual (consejo sanitario) y tratamiento farmacológico de primera línea. Las intervenciones son las mismas que para otros fumadores y, a grandes rasgos, consisten en proporcionar consejos antitabaco, o implementar terapia sustitutiva con nicotina, vareniclina o bupropion 82 . Se ha visto que los programas de deshabituación son eficaces en los pacientes asmáticos fumadores, incluso durante la hospitalización por agudización 83 , 84 , 85 y los beneficios obtenidos justifican la derivación para que reciban ayuda para dejar de fumar.…”
Section: Abordaje No Farmacológico Del Asma Desde Enfermeríaunclassified